The Controversy of Non-Muslim Leadership in Indonesia: A Comparison of Sahiron Syamsuddin's Hermeneutic Approach and Adian Husaini's Textual Interpretation - Muhammad Rizki (Al-Qadim: Jurnal Tafsir dan Ilmu Tafsir, 2025)
This article aims to examine the views of Sahiron Syamsuddin and Adian Husaini on non-Muslim leadership in the Indonesian context. The method used in this study is a qualitative approach with a descriptive-analytical and comparative model. Both figures were chosen because they are both influential Indonesian Muslim scholars in the discourse of Qur'anic interpretation. This study uses a comparative approach, highlighting Sahiron Syamsuddin's hermeneutic approach—particularly through the theory of ma'na cum maghza—and Adian Husaini's textual-normative approach. The results of the study show significant differences between the two. Sahiron interprets QS. Al-Mā'idah [5]: 51 contextually by considering maqāṣid al-sharī‘ah and social reality, thus concluding that non-Muslims can become leaders as long as they fulfill the requirements of integrity, justice, and trustworthiness. In contrast, Adian interprets the verse textually and refers to the opinion of Buya Hamka, who expressly prohibits non-Muslim leadership over Muslims. These differences in views reflect the epistemological and ideological background of each figure in interpreting the sacred text.